Sleep quality was associated with adverse reactions after coronavirus disease 2019 vaccination among healthcare workers: A longitudinal paired study - Xiao, Ning; Xu, Xingli; Ma, Zhiyue; Yu, Xiaoxu; Feng, Yong; Li, Bilan; Liu, Yuping; He, Gang; Fan, Jiangang; Li, Bin; Zhao, Xiaolong (Frontiers in Behavioral Neuroscience, 2023)
Background： Many countries now have relied on the various types of vaccines for the public to control COVID-19 pandemic. The adverse reactions (ARs) after vaccination may affect the vaccination coverage and confidence. However, whether the sleep quality was associated with the ARs after vaccination remains unclear. Methods: We designed a longitudinal paired study within a hospital setting. We collected data about the side effects within 7 days after two-dose schedule vaccination among healthcare workers (HCWs). All HCWs were asked to complete sleep survey indexed by the Pittsburgh Sleep Quality Index (PSQI) before vaccination and after one-month following up. We then explored the relationship between the sleep quality before or after vaccination and the occurrence of ARs. Results: A total of 345 HCWs were recruited to receive COVID-19vaccination. The sleep quality became poorer after vaccination. All local and systemic reactions were mild or moderate in severity (32.46%) and no serious adverse event was reported. Binary logistic regression showed participants with poor sleep quality (PSQI > 5) than good sleep quality (PSQI ≤5) before two dose vaccination respectively exhibited 1.515 and 1.107 times risk of ARs after each vaccination (both p < 0.001). Conclusions: There is an apparently complex bidirectional relationship between sleep quality and COVID-19 vaccination adverse effects. Poor sleep quality significantly increases the risk of mild ARs after vaccination, while vaccination may cause a temporary decline in sleep quality.